Strategi Inklusi Dalam Mengatasi Tantangan Pembelajaran BIPA Bagi Pemelajar Disabilitas - Diana Dzurriyatur Roviat; Anas Ahmadi; Agusniar Dian Savitri (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Indonesian for Foreign Speakers (BIPA) learning serves as a means of introducing the Indonesian language and culture to international communities. However, the implementation of BIPA learning for learners with disabilities still faces various challenges related to accessibility, diverse learning needs, teacher competence, learning environments, and the curriculum and teaching materials used. Therefore, inclusive strategies are needed to support the creation of equitable and disability-friendly learning experiences. This study aims to describe the challenges encountered in BIPA learning for learners with disabilities and to identify inclusive strategies that can be implemented to address these challenges. This study employed a literature review method by examining various sources, including books, journal articles, conference proceedings, and other relevant academic documents. Data were collected through documentation techniques and analyzed by identifying, classifying, and interpreting the collected sources. The findings reveal that the challenges in BIPA learning for learners with disabilities include limited accessibility of teaching materials and learning media, inadequate teacher competence in inclusive education, diverse needs and characteristics of learners with disabilities, learning environments that are not fully inclusive, and curricula and teaching materials that are not yet adaptive. The inclusive strategies identified include the use of multimodal learning media, enhancement of BIPA teachers’ competencies, implementation of differentiated instruction, creation of accessible and inclusive learning environments, and adaptation of curricula and teaching materials. These strategies are expected to support the development of BIPA learning that is more inclusive, accessible, and responsive to the needs of learners with disabilities. Keywords: BIPA, Disability, Inclusive Learning, Inclusive Strategies, Learners With Disabilities.. Abstrak Pembelajaran Bahasa Indonesia bagi Penutur Asing (BIPA) merupakan salah satu sarana untuk memperkenalkan bahasa dan budaya Indonesia kepada masyarakat internasional. Namun, pelaksanaan pembelajaran BIPA bagi pemelajar disabilitas masih menghadapi berbagai tantangan yang berkaitan dengan aksesibilitas, keberagaman kebutuhan belajar, kompetensi pengajar, lingkungan belajar, serta kurikulum dan bahan ajar yang digunakan. Oleh karena itu, diperlukan strategi inklusi yang mampu mendukung terciptanya pembelajaran yang setara dan ramah bagi seluruh pemelajar. Penelitian ini bertujuan untuk mendeskripsikan tantangan yang dihadapi dalam pembelajaran BIPA bagi pemelajar disabilitas serta mengidentifikasi strategi inklusi yang dapat diterapkan untuk mengatasinya. Penelitian ini menggunakan metode studi literatur dengan mengkaji berbagai sumber pustaka berupa buku, artikel jurnal, prosiding, dan dokumen ilmiah yang relevan dengan topik penelitian. Teknik pengumpulan data dilakukan melalui dokumentasi, sedangkan analisis data dilakukan dengan cara mengidentifikasi, mengklasifikasi, dan menginterpretasikan berbagai sumber yang telah dikumpulkan. Hasil penelitian menunjukkan bahwa tantangan dalam pembelajaran BIPA bagi pemelajar disabilitas meliputi keterbatasan aksesibilitas bahan ajar dan media pembelajaran, kompetensi pengajar dalam pembelajaran inklusif, keberagaman kebutuhan dan karakteristik pemelajar disabilitas, lingkungan belajar yang belum inklusif, serta kurikulum dan bahan ajar yang belum adaptif. Adapun strategi inklusi yang dapat diterapkan meliputi pemanfaatan media pembelajaran multimodal, peningkatan kompetensi pengajar BIPA, penerapan pembelajaran diferensiasi, penciptaan lingkungan belajar yang aksesibel dan inklusif, serta adaptasi kurikulum dan bahan ajar. Strategi-strategi tersebut diharapkan dapat mendukung terwujudnya pembelajaran BIPA yang lebih inklusif, aksesibel, dan responsif terhadap kebutuhan pemelajar disabilitas. Kata Kunci: BIPA, Disabilitas, Pembelajaran Inklusif, Strategi Inklusi, Pemelajar Disabilitas.